Truth in the propagandistic image. Reflections on an enigmatic corpus (Westerbork, 1944) - Dussel, Inés (Historia y Memoria de la Educación, 2018)
The article presents a theoretical and historiographical reflection on the links between image and truth, taking as a lens the analysis of the propagandistic image that privileges its political function over others. I will approach this question through some images that were taken as part of a Nazi propaganda film, shot in Westerbork, a work camp in the Netherlands, in 1944. Despite their origin, some of these images have been integrated into the iconography of WWII, and have been used as documents in trials, documentaries and exhibits critical of the Nazis; some others have been invisibilized, perhaps because they are not easily integrated into the frameworks that make the event legible. Along with the reconstruction of the history of this film, I will analyze the re-montage that German filmmaker Harun Farocki (1944-2014) did in his film Aufschub/Respite (2007). Farocki invites to suspend the images to be able to see in them the traces of the human beings that went through the camp; he brings in knowledge and positions that open up other meanings. His methodological approach, which is also ethical and political, deals with the dilemmas of working with and through propaganda images, and can bring valuable reflections and strategies for the historians of education